Occurrence of Listeria monocytogenes in cheeses coalho and butter marketed sliced in the retail trade of Arapiraca – AL (Research, Society and Development, 2021)
The objective of this study was to verify the occurrence of L. monocytogenes, as well as to characterize the microbiological profile of sliced cheeses and of butter marketed in the retail trade of the municipality of Arapiraca-AL. 60 cheese samples were collected in Establishments between August and December 2018.  The research of Listeria spp., determination of the NMP of coliforms at 45°C, and Mesophilic and psyrotrophic counts were performed. The presence of Listeria monocytogenes was detected in two samples, subsequently confirmed by qPCR. In relation to the NMP of Coliformes at 45 °, 83.3% (25/30) of the samples of rennet cheese and 80% (24/30) of the samples of butter cheese were above the limit. The mesophilic counts in butter cheese samples ranged from 1 x 103 to 6 x 105 and between 1 x 103 and 1.24 x 107 CFU/g in Coalho cheeses. The values obtained in the analysis of psychrotrophic microorganisms ranged from 1 x 103 to 3.4 x 105 in cheeses and between 1 x 103 and 2 x 105, in butter cheeses. L. monocytogenes occurs in cheeses sold sliced in stores of Arapiraca – AL and inadequate hygienic-sanitary conditions during the production chain of these cheeses represent a risk to public health.